Structure-function relationship of substituted bromomethylcoumarins in nucleoside specificity of RNA alkylation. - Stefanie Kellner; Laura Bettina Kollar; Antonia Ochel; Manjunath Ghate; Mark Helm (PLoS ONE, 2013)
Selective alkylation of RNA nucleotides is an important field of RNA biochemistry, e.g. in applications of fluorescent labeling or in structural probing experiments, yet detailed structure-function studies of labeling agents are rare. Here, bromomethylcoumarins as reactive compounds for fluorescent labeling of RNA are developed as an attractive scaffold on which electronic properties can be modulated by varying the substituents. Six different 4-bromomethyl-coumarins of various substitution patterns were tested for nucleotide specificity of RNA alkylation using tRNA from Escherichia coli as substrate. Using semi-quantitative LC-MS/MS analysis, reactions at mildly acidic and slightly alkaline pH were compared. For all tested compounds, coumarin conjugates with 4-thiouridine, pseudouridine, guanosine, and uridine were identified, with the latter largely dominating. This data set shows that selectivity of ribonucleotide alkylation depends on the substitution pattern of the reactive dye, and even more strongly on the modulation of the reaction conditions. The latter should be therefore carefully optimized when striving to achieve selectivity. Interestingly, the highest selectivity for labeling of a modified nucleoside, namely of 4-thiouridine, was achieved with a compound whose selectivity was somewhat less dependent on reaction conditions than the other compounds. In summary, bromomethylcoumarin derivatives are a highly interesting class of compounds, since their selectivity for 4-thiouridine can be efficiently tuned by variation of substitution pattern and reaction conditions.